Disseminated Coccidioidomycosis to the Gallbladder - Kulraj Grewal MD; Tushar Bajaj MD; Greti Petersen MD; Augustine Munoz MD; Arman Froush DO; Arash Heidari MD (SAGE Publishing, 2020)
Coccidioidomycosis is an infection caused by inhalation of arthroconidia produced by dimorphic fungi in the genus Coccidioides . Forty percent of patients will develop an influenza-like illness with symptoms suggestive of a mild and self-limited respiratory infection; however, 5% of these individuals will develop extrapulmonary disseminated disease. An immunocompromised patient presented with right upper quadrant pain, ultrasound with pericholecystic fluid, in which a percutaneous cholecystostomy contained biliary fluid that grew the fungus Coccidioides immitis . Patient was initiated on intravenous amphotericin therapy and was followed closely with postoperative bile drainage with eventual laparoscopic cholecystectomy. We present a very rare case of disseminated coccidioidomycosis to the gallbladder.